Phosphorylation of residues inside the SNARE complex suppresses secretory vesicle fusion. (11th July 2016) - Malmersjö, Seth; Di Palma, Serena; Diao, Jiajie; Lai, Ying; Pfuetzner, Richard A; Wang, Austin L; McMahon, Moira A; Hayer, Arnold; Porteus, Matthew; Bodenmiller, Bernd; Brunger, Axel T; Meyer, Tobias
Abstract: Membrane fusion is essential for eukaryotic life, requiring SNARE proteins to zipper up in an α‐helical bundle to pull two membranes together. Here, we show that vesicle fusion can be suppressed by phosphorylation of core conserved residues inside the SNARE domain. We took a proteomics approach using a PKCB knockout mast cell model and found that the key mast cell secretory protein VAMP8 becomes phosphorylated by PKC at multiple residues in the SNARE domain. Our data suggest that VAMP8 phosphorylation reduces vesicle fusion in vitro and suppresses secretion in living cells, allowing vesicles to dock but preventing fusion with the plasma membrane. Markedly, we show that the phosphorylation motif is absent in all eukaryotic neuronal VAMPs, but present in all other VAMPs. Thus, phosphorylation of SNARE domains is a general mechanism to restrict how much cells secrete, opening the door for new therapeutic strategies for suppression of secretion. Synopsis: The SNARE complex required for membrane fusion consists of four alpha‐helices. PKCB‐dependent phosphorylation of highly conserved residues forming the interaction surface facing the inside of the helical bundle suppresses secretion by inhibiting vesicle fusion without impeding docking. Vesicular‐associated membrane proteins (VAMPs) contain evolutionary conserved inhibitory phosphorylation sites facing the inside of the SNARE complex. The phosphorylation sites are absent in neuronal VAMPs, but are present in other VAMPs, such as VAMP8. Phosphorylation of VAMP8 suppresses secretion by inhibiting the vesicle fusion step without preventing vesicle docking. Phosphorylation of VAMP8 is mediated by PKCB. Abstract : The SNARE complex required for membrane fusion consists of four alpha‐helices. PKCB‐dependent phosphorylation of highly conserved residues forming the interaction surface facing the inside of the helical bundle suppresses secretion by inhibiting vesicle fusion without impeding docking.